DETERMINANTS OF BUSINESS ACTORS USING QRIS AT TOURISM DESTINATIONS IN MATARAM CITY: UTAUT 2 MODEL - Suprapti, Ida Ayu Putri; Chaidir, Taufiq; Arini, Gusti Ayu; Adamy, Huzay Billybina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025, 2025)
Tourism is one of the most essential industries in the city of Mataram. One way for this sector to develop faster is for tourism actors to adapt to technological developments related to the QRIS-based non-cash payment system. Therefore, a study of the determinants of using QRIS-based non-cash payment systems based on QRIS in tourism destinations is needed. This research aims to determine business actors' readiness to implement a non-cash payment system through the UTAUT 2 model. The data collection method used in this research is the sample survey method. The results showed that performance expectation and habits have a significant effect on behavioral intention, while effort expectations, social influence, facilitating conditions, hedonic motivation, and price value have no effect on behavioral intention so it is recommended that Payment System Service Providers must improve technology related to ease of use, network infrastructure and facilities from QRIS.